Measurung The Competitiveness Of Malaysian Tourism Cities Through The Application,Of Multi Dimensional Scaling Analysis. - Mohamed, Badaruddin; Irwana Omar, Shida; Muhibudin, Masitah; Shamsuddin, Nurhashikin (2009)
Tourist destinations contain many desired or expected attributes by travelers.